The effects of velocity-based versus percentage-based resistance training on athletic performances in sport-collegiate female basketball players - Zhang, Mingyang; Liang, Xingyue; Huang, Weifeng; Ding, Shicong; Li, Guoxing; Zhang, Wei; Li, Chao; Zhou, Yanfeng; Sun, Jian; Li, Duanying (Frontiers in Physiology, 2023)
Introduction: The study compared the effects of 6-week (2 sessions/week) velocity-based resistance training (VBRT) and percentage-based resistance training (PBRT) on athletic performance in Sport-College female basketball players. Methods: Fifteen participants were assigned to the VBRT (n = 8) or PBRT (n = 7) groups. The load in VBRT group were determined through the sessional target velocity and velocity loss monitoring, whereas PBRT group used a fixed-load based on percentage of 1-repetition maximum (1RM). Both groups completed intervention that involved the free weight back squat and bench press using the same relative load (linear periodization from 65% to 95% 1RM). Training loads data was continuously recorded. Measurements at baseline (T0) and post-training (T2) included 1RM, countermovement-jump (CMJ), squat-jump (SJ), eccentric-utilization-ratio (EUR), drop-jump height and reactive-strength-index (DJ, DJ-RSI), plyometric-push-up (PPU), 505 change-of-direction (COD), 10-m、20-m sprint (T-10、T-20), 17 × 15 m drill-lines (17-drill), Hexagon agility, and functional movement screen (FMS). A mid-term (T1) assessment was included to investigate the short-term effects of both methods and the fluctuation of personalized 1RM. Results: No between-group differences were observed at T0 for descriptive variables (p > 0.05). Both groups showed significant improvement in strength gains for back squat and bench press, but VBRT showed likely to very likely favorable improvements in CMJ, SJ, EUR, DJ-RSI, Hexagon and COD among athletic performance. The VBRT showed likely to very likely improvements in 17-drill and DJ, while PBRT showed unclear effects. The lifted weights adjusted by VBRT method were higher than prescribed by PBRT (p < 0.05) for the same subjects. Conclusion: Compared with fixed-load PBRT, VBRT enhanced power and athletic performance despite similar strength gains. VBRT can be regarded as a more functional resistance-training method under linear periodization.